If it's not what You are looking for type in the equation solver your own equation and let us solve it.
25-5x=5(5x+3)
We move all terms to the left:
25-5x-(5(5x+3))=0
We calculate terms in parentheses: -(5(5x+3)), so:We get rid of parentheses
5(5x+3)
We multiply parentheses
25x+15
Back to the equation:
-(25x+15)
-5x-25x-15+25=0
We add all the numbers together, and all the variables
-30x+10=0
We move all terms containing x to the left, all other terms to the right
-30x=-10
x=-10/-30
x=1/3
| -20+3g=4g | | -17-(-14)=x/11 | | -4x+2(x-5)=-26 | | -4s+8=3s-8-5s | | 0.5÷16+x=16 | | 2x+7=3x–1 | | -12-2m=17m-12 | | 3x/6=4/5+2x+9/2 | | 6/7y=8/21 | | -8x+6(x+4)=6 | | -8g-6=-7g | | 8-7d=1-9d-5 | | 19(40-x)+69=20+55 | | -10+6p=10+4p | | 1/2a=14 | | -16n+8=-15n-8 | | X+(2X-100)=180-y | | x/15.8=9.2/23.6 | | 7x^2+180x-900=0 | | (15b-4)-7(2b+1)=-6 | | s/6+14=45 | | (15b-4)-7(2b+`)=-6 | | -999(n^2+1)=2000n | | 5^2x-1=125^3x+2 | | 4x²-360=0 | | V=10-v | | 15x-12+6x=180 | | 8-5c=-9-9c-7 | | -x+5=-4x+14 | | 1/3(6y-9)=5 | | 4r-5=7+r | | 3-9u=7-8u |